KEBIJAKAN INDONESIA BELUM MERATIFIKASI KONVENSI OECD ON COMBATING TRANSNATIONAL BRIBERY PERIODE 2014-2017 - Fransiska Friska Intan Cahyani; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Indonesia faced menace of transnational bribery problems within the escalation of international trade flows, yet Indonesia does not have rule settling transnational bribery. Indonesia is one of four countries in G20 who have not ratified OECD Convention on Combating Bribery of Foreign Public Officials in International Business Transactions. Whereas, as an ACWG G20 member, Indonesia is required to obey the Action Plan which one of the points is to ratify the OECD convention. This study aims to understand the background of Indonesia’s postponement policy of ratifying the convention related to Indonesia’s status as ACWG G20 member. Using non-compliance concept of compliance theory and qualitative method its is known the factors that resulted in the attitude of postponement policy, such as ambiguities in the interpretation of ACWG Action Plans, the incapability of Indonesia to fulfill the preconditions of OECD convention, and the influence of temporal dimension which influenced Indonesia primary priorities to improve the economy and the development of infrastructure as stated in Nawa Cita.